Using online vacancies and web surveys to analyse the labour market: A methodological inquiry - Lucia Mýtna Kureková; Miroslav Beblavý; Anna Thum-Thysen (IZA Journal of Labor Economics, 2015)
This paper discusses methodological issues arising from the use of online job vacancy data and voluntary web-based surveys to analyse the labour market. We highlight the advantages and possible disadvantages of using online data and suggest strategies for overcoming selected methodological issues. We underline the difficulties in adjusting for representativeness of online job vacancies, but nevertheless argue that this rich source of data should be exploited.
Keywords: E4; J2; 330; Internet; Job; Labour market; Methodology; Occupation; Online; Representativeness; Vacancy